Restorative Justice as an Effort to Reduce Recidivism in Child Offenders of Theft - Khomaini Khomaini (Fox Justi : Jurnal Ilmu Hukum, 2026)
The number of children in conflict with the law in Indonesia continues to increase, with theft being the most dominant type of crime. Data from the National Legal Development Agency (BPHN) in the 2020-2022 period shows 838 cases of theft committed by children out of a total of 2,302 cases of children facing the law. Meanwhile, the punitive approach through imprisonment has not been effective in reducing recidivism rates among child offenders. This study aims to analyze the application of restorative justice as an effort to reduce recidivism in child theft offenders and identify the obstacles faced in its implementation. The research method used is normative legal research with statutory, conceptual, and case approaches. The results show that restorative justice through diversion as regulated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System has a strong legal basis but its implementation still faces various obstacles. Based on data from the Directorate General of Corrections, out of 29,228 children handled by police in the 2017-2020 period, only 14.1% of cases were closed through diversion. The obstacles include the limited understanding of law enforcement officers regarding restorative justice, the retributive mindset that still dominates society, and the lack of supporting infrastructure. Optimization strategies can be implemented through strengthening diversion mechanisms, enhancing the capacity of law enforcement officers, and transforming the legal culture towards a rehabilitative approach. The enactment of the National Criminal Code (Law Number 1 of 2023) effective January 2, 2026, and Supreme Court Regulation Number 1 of 2024 concerning Guidelines for Adjudicating Criminal Cases Based on Restorative Justice further strengthen the legal basis for the application of restorative justice for child offenders.